2022
DOI: 10.3390/su14052503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracellular Polymeric Substances and Specific Compositions on Enhancement of Copper Bioleaching Efficiency from Waste Printed Circuit Boards

Abstract: Bioleaching has been proven to be an efficient and environment-friendly method for processing metalliferous ore and waste printed circuit boards (PCBs), a type of urban mine waste. Extracellular polymeric substances (EPS) play a major role in the attachment of bacteria to the surface of sulfide minerals. However, there are few reports on the effects of EPS components on the bioleaching of metals from PCBs. In this study, synthetic EPS were used to investigate the effects of the composition of exo-polymers on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…They concluded that AMD improved the bioleaching of bornite, and in general, the use of this solution for the bioleaching of low-grade sul de ores had a positive result. Xu, Zhu [9] applied Acidithiobacilus ferrooxidans existed in an AMD sample to the bioleaching of copper from waste printed circuit boards and achieved a high dissolution e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that AMD improved the bioleaching of bornite, and in general, the use of this solution for the bioleaching of low-grade sul de ores had a positive result. Xu, Zhu [9] applied Acidithiobacilus ferrooxidans existed in an AMD sample to the bioleaching of copper from waste printed circuit boards and achieved a high dissolution e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic polymers are further used in fabricating pipes, ropes, belts, and insulators. The 3D-printed parts of polymers has emerged with increased research leading to increased use of polymers in various industries [28,29]. Polymer printing is preferred for low massive production and prototyping as it is cost-effective, and functional parts with distinct capabilities and properties can be printed.…”
Section: Introductionmentioning
confidence: 99%